TEKNIK ANALISIS KANONIKAL: HUBUNGAN HIMPUNAN ANTAR VARIABEL (Suatu Pengantar Teoritis) - Basuki . Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Canonical analysis, a fundamental statistical technique, has been widely employed across various fields of study, from social sciences to life sciences, to uncover the underlying relationships between sets of variables. This comprehensive review article aims to provide a detailed exploration of the theoretical foundations, methodological considerations, and practical applications of canonical analysis.